Semantic Roles of The Verb â€œTo Seeâ€ in Javenese of Kertosono - A.A.A Ngr. Adriyanti Weda Ningrat; I Nyoman Kardana; Mirsa Umiyati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
This study reveals the semantic fields from the